ECOLOGIA ALIMENTAR DE SEIS ESPÉCIES DE Crenicichla (PISCES: CICHLIFORMES: CICHLIDAE) DO BAIXO RIO IGUAÇU À MONTANTE DAS CATARATAS. - de Souza, Tuiza; Maria Dias, Rosa; Meneses , Cleiton; Celi Fedatto Abelha, Milza; Cavicchioli Makdrakis , Maristela; Antoniassi Luiz Kashiwaqui, Elaine (ANAIS DO ENIC, 2026)
-